How identification with and attachment to place affects preference to move in later life: smallest space analysis - White, Stefan; Walsh, Stephen; Shuttleworth, Stephanie; Dagnall, Neil (Frontiers in Psychology, 2025)
As populations age and urbanize, there is a need for housing and neighborhoods that support healthier, happier lives for older adults. While “Aging in Place” policies enable seniors to remain in their homes and communities, critics argue they overlook the complex physical, social, and psychological factors necessary for positive aging. Particularly, policies that focus on the dwelling or proximity to care and failure to address older adults’ holistic needs. Positive alternatives, such as the “Age-Friendly Environments,” proposed by the World Health Organization, emphasize public health interventions that create neighborhoods where older people maintain social connections and live in supportive environments, regardless of accommodation type. This research, drawing on UK Understanding Society survey data, utilized Smallest Space Analysis (SSA) to identify what influences older adults’ preferences to stay or move. Findings suggest that a significant predictor of housing choice was the neighborhood as a social “place.” Specifically, it is a location with which individuals identified, attached, and embedded. This outcome held more weight than individual attributes like house type, financial status, or social position. Results highlighted the need for further empirical investigation into the centrality of neighborhood identification in older adults’ housing decisions.